2016
DOI: 10.1159/000449060
|View full text |Cite
|
Sign up to set email alerts
|

Kcne4 Deletion Sex-Dependently Alters Vascular Reactivity

Abstract: Voltage-gated potassium (Kv) channels formed by Kv7 (KCNQ) α-subunits are recognized as crucial for vascular smooth muscle function, in addition to their established roles in the heart (Kv7.1) and the brain (Kv7.2-5). In vivo, Kv7 α-subunits are often regulated by KCNE subfamily ancillary (β) subunits. We investigated the effects of targeted germline Kcne4 deletion on mesenteric artery reactivity in adult male and female mice. Kcne4 deletion increased mesenteric artery contractility in response to α-adrenocept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
(75 reference statements)
1
39
0
Order By: Relevance
“…In this study, we also observed a small contraction with 5 mM 4‐AP consistent with its effect to inhibit delayed rectifier K v currents. Given the still somewhat unknown and varied K v 7 channel subtype expression, channel stoichiometry across vascular beds (Jepps et al, ) and coassembly with β‐subunits (Jepps et al, ; Abbott and Jepps, ), it is possible that 4‐AP is less able to relax other arteries that are more dependent on K v 1, K v 2 or K v 7.5 activities, instead inducing a contractile response at concentrations >1 mM. We suggest that the complexity of different native systems together with the multifarious nature of 4‐AP, particularly at higher concentrations, is responsible for any discrepancies with previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we also observed a small contraction with 5 mM 4‐AP consistent with its effect to inhibit delayed rectifier K v currents. Given the still somewhat unknown and varied K v 7 channel subtype expression, channel stoichiometry across vascular beds (Jepps et al, ) and coassembly with β‐subunits (Jepps et al, ; Abbott and Jepps, ), it is possible that 4‐AP is less able to relax other arteries that are more dependent on K v 1, K v 2 or K v 7.5 activities, instead inducing a contractile response at concentrations >1 mM. We suggest that the complexity of different native systems together with the multifarious nature of 4‐AP, particularly at higher concentrations, is responsible for any discrepancies with previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…(a) The data have been obtained from male animals only. Thus, sex as a biological variable was not considered, while the function of potassium channels in the vasculature can be sex‐dependent . However, it was the aim of our study to present a comprehensive investigation of the negative feedback regulation of vasocontraction by various types of potassium channels in early postnatal ontogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To aid in this endeavor, we studied the effects of germline deletion of Kcne5 in mice. Transgenic mouse models have been instrumental in detecting and characterizing novel native functions of KCNE subunits (23,25,30,(37)(38)(39)(40)(41)(42)(43)(44)(45). By phenotypically studying Kcne5 -/0 mice, we discovered that Kcne5 regulates K V 2.1 current (I K,slow,2 ) (27,29) in mouse ventricles.…”
Section: Discussionmentioning
confidence: 99%